Rapid characterization and identification of the chemical constituents and rat metabolites of Deng‐Zhan‐Xi‐Xin injection using ultra high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Issue 18 (8th August 2018) - Guo, Xin; Lin, Shan; Yang, Peiming; Ye, Ji; Du, Jiang; Mu, Xuemei; Mi, Nan; Qi, Xiaopo; Lei, Huibo; Zhang, Weidong; Tian, Xinhui
Abstract: Deng‐Zhan‐Xi‐Xin injection is a well‐known traditional Chinese medicine prescription for the treatment of cardiovascular and cerebral vessel diseases. However, there have been few reports on its chemical constituents and metabolic pathway, which has blocked its further quality control and studies on its pharmacology and mechanism of action. In this study, an integrative method was established to rapidly explore the chemical constituents and metabolites of Deng‐Zhan‐Xi‐Xin injection using ultra high performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry and the UNIFI™ software combined with multiple data processing approaches. As a result, a total of 40 compounds, including 9 flavonoids and 31 phenolic acids were identified or tentatively characterized, and five compounds were first reported in Deng‐Zhan‐Xi‐Xin injection. Under the same analysis conditions, 70 compounds have been detected in rats, including 25 prototypes and 45 metabolites. This was the first systematic research study on the metabolic profiling of Deng‐Zhan‐Xi‐Xin injection. This study provides valuable chemical information for the quality control and research on pharmacology and mechanism of action of Deng‐Zhan‐Xi‐Xin injection. Moreover, it provides a valuable strategy for analyzing the chemical components and metabolites of other traditional Chinese medicine prescriptions.